2019
DOI: 10.3390/cancers12010062
|View full text |Cite
|
Sign up to set email alerts
|

The Role of E3, E4 Ubiquitin Ligase (UBE4B) in Human Pathologies

Abstract: The genome is exposed daily to many deleterious factors. Ubiquitination is a mechanism that regulates several crucial cellular functions, allowing cells to react upon various stimuli in order to preserve their homeostasis. Ubiquitin ligases act as specific regulators and actively participate among others in the DNA damage response (DDR) network. UBE4B is a newly identified member of E3 ubiquitin ligases that appears to be overexpressed in several human neoplasms. The aim of this review is to provide insights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Previous studies have shown that the U-box catalytic domain of UBE4B is closely related to the RING-finger domain of MDM2 and is responsible for its E3 activity, and these two enzymes are considered significant regulators of P53 through the ubiquitination process [ 17 , 31 33 ]. UBE4A , as a homolog of UBE4B [ 17 ], may also exert the same effect on P53 . To verify this claim, we performed qRT-PCR and WB analysis in UBE4A knockdown CRC cell lines and their corresponding negative control cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the U-box catalytic domain of UBE4B is closely related to the RING-finger domain of MDM2 and is responsible for its E3 activity, and these two enzymes are considered significant regulators of P53 through the ubiquitination process [ 17 , 31 33 ]. UBE4A , as a homolog of UBE4B [ 17 ], may also exert the same effect on P53 . To verify this claim, we performed qRT-PCR and WB analysis in UBE4A knockdown CRC cell lines and their corresponding negative control cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have implicated UBE4B as a regulator of P53 [ 15 18 ]; the U box catalytic domain is closely related to the RING-finger domain of MDM2 and is responsible for its E3 activity. These two enzymes are considered significant regulators of P53 through the ubiquitination process [ 17 ]. However, the function of UBE4A , as a U box catalytic domain-containing E3 ubiquitin ligase, remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are an estimated 600-700 E3 ligase genes representing approximately 5% of the human genome [36]. Ubiquitin ligases can promote the degradation of either oncogenes or tumorsuppressor genes, thus E3s are themselves "druggable" enzymes or serve as potential cancer targets [37,38]. The E3 ubiquitin-ligase enzyme is important for the specific binding of ubiquitin to its target substrate, which depends on their specific domains [39].…”
Section: Ubiquitination and Deubiquitinationmentioning
confidence: 99%
“…E4 ubiquitin ligases play roles in highly processive chain elongation but not in the initial steps of ubiquitination [ 79 , 80 , 81 , 82 , 83 ]. E4 ligases not only play complementary roles to E3 ligases but also facilitate the function of E3 ligases under certain circumstances, which extends the length of polyubiquitin chains [ 80 , 84 ].…”
Section: Ubiquitinationmentioning
confidence: 99%